Harmonization issues in unit costing of service use for multi-country, multi-sectoral health economic evaluations: A scoping review - Claudia Fischer; Susanne Mayer; Nataša Perić; Judit Simon (Health Economics Review, 2022)
Background: Valuation is a critical part of the costing process in health economic evaluations. However, an overview of specific issues relevant to the European context on harmonizing methodological requirements for the valuation of costs to be used in health economic evaluation is lacking. We aimed to inform the development of an international, harmonized and multi-sectoral costing framework, as sought in the European PECUNIA (ProgrammE in Costing, resource use measurement and outcome valuation for Use in multi-sectoral National and International health economic evaluAtions) project. Methods: We conducted a scoping review (information extraction 2008-2021) to a) to demonstrate the degree of heterogeneity that currently exists in the literature regarding central terminology, b) to generate an overview of the most relevant areas for harmonization in multi-sectoral and multi-national costing processes for health economic evaluations, and c) to provide insights into country level variation regarding economic evaluation guidance. A complex search strategy was applied covering key publications on costing methods, glossaries, and international costing recommendations augmented by a targeted author and reference search as well as snowballing. Six European countries served as case studies to describe country-specific harmonization issues. Identified information was qualitatively synthesized and cross-checked using a newly developed, pilot-tested data extraction form. Results: Costing methods for services were found to be heterogeneous between sectors and country guidelines and may, in practice, be often driven by data availability and reimbursement systems in place. The lack of detailed guidance regarding specific costing methods, recommended data sources, double-counting of costs between sectors, adjustment of unit costs for inflation, transparent handling of overhead costs as well as the unavailability of standardized unit costing estimates in most countries were identified as main drivers of country specific differences in costing methods with a major impact on valuation and cost-effectiveness evidence. Conclusion: This review provides a basic summary of existing costing practices for evaluative purposes across sectors and countries and highlights several common methodological factors influencing divergence in cost valuation methods that would need to be systematically incorporated and addressed in future costing practices to achieve more comparable, harmonized health economic evaluation evidence.
Keywords: 330; (criminal) justice; Economic evaluation; Education; Health and social care; Societal perspective; Unit cost; Valuation